Bi2O3 Nanoparticles Decorated Carbon Nanotube: An Effective Nanoelectrode for Enhanced Electrocatalytic 4-Nitrophenol Reduction - Dighole, Raviraj P.; Munde, Ajay V.; Mulik, Balaji B.; Sathe, Bhaskar R. (Frontiers in Chemistry, 2020)
4-Nitrophenol (4-NP) is present in most industrial waste water resources as an organic pollutant, and is a highly toxic and environmentally hazardous pollutant. Herein, we report that bismuth oxide (Bi2O3) decorated multi-walled carbon nanotubes (Bi2O3@MWCNTs) are the most prominent electrocatalyst for 4-NP electroreduction in acidic conditions. The electrocatalyst is synthesized by a simple chemical reduction method using ethylene glycol as a capping agent. The synthesized Bi2O3@MWCNTs electrocatalyst has been well-characterized by Fourier-transform infrared (FT-IR) spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD), and Raman spectroscopy. Bi2O3@MWCNTs have a cubic structure which is confirmed by XRD. TEM imaging reveals Bi2O3 NPs are 2 nm in size, are grown on MWCNTs and that these nanoparticles are active toward 4-NP electroreduction. The electrochemical studies by cyclic voltammetry measurements show that the Bi2O3@MWCNTs electrocatalyst can sense 4-NP at a very low potential i.e., −0.17 vs. saturated calomel electrode (SCE). Furthermore, electroanalytical parameters like scan rate and concentration dependence were studied with electrochemcial impedance spectroscopy (EIS) and the effect of pH on cathodic current was examined under experimental conditions. The lower limit of detection (LOD) was found to be 0.1 μM for the Bi2O3@MWCNTs nanomaterial and is excellent toward 4-NP. The present study has applications for reducing water pollution and for sorting out related issues.